ANALISA BATAS MAKSIMUM KREDIT PAJAK UNTUK SETIAP NEGARA PADA PAJAK PENGHASILAN (PPh) PASAL 24 MENGGUNAKAN MS. ACCESS PROGRAMMING - Suhartono, - (www.bsi.ac.id, 2015)
ABSTRACT The goal of each state is established is to improve the lives or well-being of its people are reflected in the revenue / increasing personal income. With the increase in personal income residents of a country will automatically increase the income of a country anyway. There are many ways for a country's income can continue to grow, one of them through the tax sector. Each year, Indonesia continues to increase state revenues through tax sector which will be used to build the country's economy through infrastructure development and development of other important sectors. Calculation of income tax paid or payable abroad that may be credited against income tax payable on the total income tax payer in the country has been set out clearly by the provisions of Article 24 of the Income Tax Act. Indonesia implemented a policy of crediting method is limited (Ordinary Credit Method) by applying maximum tax credit calculation is done for each country (per country limitation). Foreign tax creditable done in the company consolidated income from abroad with income in Indonesia but does not exceed the calculation of tax payable by the Income Tax Law. This is done in order to avoid double pejak so as not to burden the detriment of taxpayers.Keywords: Limit Tax Credit, Income Tax (VAT) of Article 24, Ms. Access Programming